Gender Differences and Self-Esteem as Predictors of Perceived Sexual Harassment among Undergraduates in Nigeria - Roberts , Enyelunekpo; Ibekwe, Uchechi; Atunwa , Sunday; Uye, Emmanuel (Universitas Ahmad Dahlan, 2025)
Sexual harassment has become a pervasive problem in many tertiary institutions worldwide which affects psychological, physical and academic well-being among undergraduates. This study investigated gender differences and self-esteem as predictors of perceived sexual harassment among undergraduates in Rivers State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select three tertiary institutions in the State. Data were collected from 250 participants using validated questionnaires and analyzed using multiple regressions analysis and independent samples t-test. Two hypotheses were tested and accepted at p <.05 level of significance. The result revealed that gender differences and self-esteem jointly predicted perceived sexual harassment among study participants R2 = .274, F(2,248) = 46.633, p <.05. In addition, gender differences (β = .349, p <.05) and self-esteem (β = -.348, p <.05) independently predicted perceived sexual harassment among study participants. Finally, the result confirmed gender differences and perceived sexual harassment [t(247) =17.981, p <.05] such that female undergraduates reported higher perceived sexual harassment (M =38.83, SD=1.29) than their male counterparts (M = 30.94, SD= 4.94). The novelty of this finding is that it is the first time sexual harassment is investigated among undergraduates in these three tertiary institutions in Rivers State. The study recommended that university authority should be proactive in designing and implementing policy that will reduce sexual harassment in their institutions.